HUBUNGAN TINGKAT AKTIVITAS FISIK DENGAN DERAJAT NYERI MUSKULOSKELETAL SELAMA PANDEMI COVID-19 PADA MAHASISWA - Arwan Bin Laeto (Jurnal Medika Hutama, 2023)
Background: Musculoskeletal pain is a disorder of the muscles, nerves, tendons, joints, cartilage, and spinal discs. Musculoskeletal pain can affect quality of life and reduce individual productivity both physically, mentally, and socially. Musculoskeletal pain can be caused by various risk factors, one of which is physical activity. The purpose of this study was to determine the relationship between physical activity level and musculoskeletal pain during the COVID-19 pandemic in college students. Methods: This study used observational analytic research with a cross-sectional study design using primary data obtained directly from respondents who met the inclusion and exclusion criteria. Data was collected using a questionnaire that was distributed online via Google Forms. The sampling method used in this study was consecutive sampling, with a total of 107 samples. The data were analyzed using the Chi-Square test. Results: There is a significant relationship between the level of physical activity and musculoskeletal pain during the COVID-19 pandemic in college students, with a p-value of 0.002 (P <0.05). Conclusion: Musculoskeletal pain is significantly related to the level of physical activity among college students, with a percentage of 47.7% experiencing moderate-high category musculoskeletal pain and 52.3% experiencing low category musculoskeletal pain.